Seasonal and inter-annual variability of bud development as related to climate in two coexisting Mediterranean Quercus species - Alla, Arben Q.; Camarero, J. Julio; Montserrat-Martí, Gabriel (Annals of Botany, 2013)
Background and Aims In trees, bud development is driven by endogenous and exogenous factors such as species and climate, respectively. However, knowledge is scarce on how these factors drive changes in bud size across different time scales.Methods The seasonal patterns of apical bud enlargement are related to primary and secondary growth in two coexisting Mediterranean oaks with contrasting leaf habit (Quercus ilex, evergreen; Quercus faginea, deciduous) over three years. In addition, the climatic factors driving changes in bud size of the two oak species were determined by correlating bud mass with climatic variables at different time scales (from 5 to 30 d) over a 15-year period.Key Results The maximum enlargement rate of buds was reached between late July and mid-August in both species. Moreover, apical bud size increased with minimum air temperatures during the period of maximum bud enlargement rates.Conclusions The forecasted rising minimum air temperatures predicted by climatic models may affect bud size and consequently alter crown architecture differentially in sympatric Mediterranean oaks. However, the involvement of several drivers controlling the final size of buds makes it difficult to predict the changes in bud size as related to ongoing climate warming.
10.1093/aob/mcs24710.1093/aob/mcs247
Keywords: Bud size; current-year stem; Quercus faginea; quercus ilex subsp. ballota; summer growth; Temperature

Acorn production is linked to secondary growth but not to declining carbohydrate concentrations in current-year shoots of two oak species - Alla, Arben Q.; Camarero, J. Julio; Maestro-Martínez, Melchor; Montserrat-Martí, Gabriel (Trees, 2011)
In trees, reproduction constitutes an important resource investment which may compete with growth for resources. However, detailed analyses on how growth and fruit production interact at the shoot level are scarce. Primary canopy growth depends on the development of current-year shoots and their secondary growth might also inﬂuence the number and size of fruits supported by them. We hypothesise that an enhanced thickening of currentyear shoots is linked positively to acorn production in oaks. We analysed the effect of acorn production on shoot growth of two co-occurring Mediterranean oak species with contrasting leaf habit (Quercus ilex, Quercus faginea). Length and cross-sectional area of current-year shoots, apical bud mass, number of leaves and acorns, xylem and conductive area, number of vessels of acorn-bearing and non-bearing shoots were measured in summer and autumn. Nitrogen and carbohydrates analyses were also performed in stems and leaves of both shoot types. Stem cross-sectional area increased in acorn-bearing shoots when compared with non-bearing shoots for both species and such surplus secondary growth was observed since summer. In bearing shoots, the total transversal area occupied by vessels decreased signiﬁcantly from basal to apical positions along the stem as did the xylem area and the number of vessels. Leaves of bearing shoots showed lower nitrogen concentration than those of non-bearing shoots. Carbohydrate concentrations did not differ in stems and leaves as a function of the presence of acorns. Such results suggest that carbohydrates may preferentially be allocated towards reproductive shoots, possibly through enhanced secondary growth, satisfying all their carbon demands for growth and reproduction. Our ﬁndings indicate that acorn production in the two studied oaks depends on shoot secondary growth.
Keywords: acorns; Mediterranean climate; nitrogen; non-structural carbohydrates; Quercus faginea; quercus ilex subsp. ballota; Stem diameter; Xylem

Impacts of drought at different time scales on forest growth across a wide climatic gradient in north-eastern Spain - Pasho, Edmond; Camarero, J. Julio; de Luis, Martín; Vicente-Serrano, Sergio M. (Agricultural and Forest Meteorology, 2011)
We analyzed the impact of drought measured on different time-scales on radial growth of eight tree species during the period 1950–2005 growing across a wide climatic gradient encompassing semiarid Mediterranean woodlands and wet mountain forests in north-eastern Spain. A drought index (standardized precipitation index, SPI) at different time scales (1–48 months) was correlated with chronologies of ring width to determine the signiﬁcant time scale at which drought affected most tree growth. The ﬁndings indicated that the impact of drought on growth varied noticeably among species and sites. Two distinct patterns were clearly observed considering spatial and temporal differences in the response of species to drought. Species growing in xeric sites (Pinus and Quercus species and Juniperus thurifera) showed the highest responses to SPI time-scales of 9–11 months while those located in mesic sites (Abies alba, Pinus sylvestris) did respond more to SPI time scales shorter than 5 months. The SPI-growth correlations were signiﬁcant, although weak, up to 30 months in xeric sites while no consistent association was observed at higher time scales. Important seasonal differences were noticed in the SPI-growth associations. Species growing in xeric areas responded to spring-summer SPI while those distributed in mesic sites responded more to summer SPI. Our ﬁndings should be useful to understand forest responses to climate change, including an increasing frequency of severe droughts, and to adapt appropriate management strategies to mitigate the impact of drought on tree growth.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Dendrochronology; Drought; Forest growth; Impacts; NE Spain; Standardized precipitation index (SPI)

An increase in canopy cover leads to masting in Quercus ilex - Camarero, J. Julio; Albuixech, Jorge; López-Lozano, Raúl; Casterad, M. Auxiliadora; Montserrat-Martí, Gabriel (Trees, 2010)
Masting is the intermittent and synchronous production of large crops, but its relation to tree growth remains elusive despite the ecological relevance of mast seeding. The production of huge fruit crops has been linked to the accumulation and consumption of resources as nutrients and carbohydrates, but no conclusive assessment has supported this assumption. To evaluate if masting takes place once trees’ canopies reach maximum foliage, changes in canopy cover were measured in Quercus ilex susbp. ballota stands before and after a masting event using the normalized difference vegetation index (NDVI). The results on the whole underline that masting in Q. ilex occurred once maximum levels of NDVI and canopy cover were reached. After the masting event, NDVI dropped, leaf shedding increased and trees produced shorter shoots, narrower tree rings and fewer acorns than before the masting event. These ﬁndings support our contention that an increase in canopy cover precedes masting.
Keywords: acorn; canopy cover; Mast seeding; quercus ilex subsp. ballota; Remote sensing